Focus on the wonder years : challenges facing the American middle school - Juvonen, Jaana; Rand Education (Institute) (Santa Monica, CA : Rand, 2004)
Young teens undergo multiple changes that seem to set them apart from other students. But do middle schools actually meet their special needs? The authors describe some of the challenges and offer ways to tackle them, such as reassessing the organization of grades K-12; specifically assisting the students most in need; finding ways to prevent disciplinary problems; and helping parents understand how they can help their children learn at home.
Goals, terms, methods, and organization -- A brief history of the U.S. middle school -- Core practices of the middle school concept -- Academic achievement -- Conditions for student learning -- Principals -- Promoting teacher competence through training -- Parental involvement -- Whole-school reform models -- Conclusions and recommendations.
"Prepared for the Edna McConnell Clark Foundation."
"RAND Education."
Errata slip included.
Includes bibliographical references (pages 137-155).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Middle schools -- United States; Middle school education -- United States; Écoles moyennes -- États-Unis.; Enseignement moyen -- États-Unis.; EDUCATION -- Secondary; EDUCATION -- Educational Policy & Reform -- General; Middle school education; Middle schools; United States; Middle school; USA